2016
DOI: 10.1016/j.carbpol.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Functionality of maize, wheat, teff and cassava starches with stearic acid and xanthan gum

Abstract: Consumer concerns to synthetic chemicals have led to strong preference for ‗clean' label starches. Lipid and hydrocolloids are food friendly chemicals. This study determines the effects of stearic acid and xanthan gum alone and in combination on the functionality of maize, wheat, teff and cassava starches. An increase in viscosity was observed for all starches with stearic acid and xanthan gum compared to the controls with cassava having the least increase. A further increase in viscosity was observed for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 42 publications
1
27
1
Order By: Relevance
“…There was no increase in viscosity during the long pasting of maize starch extrudate with stearic acid. These results were different from those of several authors working on maize and teff starches pasted with stearic acid, which showed an increase in viscosity during long pasting. The increase in viscosity reported by these authors during long pasting has been attributed to the formation of ALCs.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…There was no increase in viscosity during the long pasting of maize starch extrudate with stearic acid. These results were different from those of several authors working on maize and teff starches pasted with stearic acid, which showed an increase in viscosity during long pasting. The increase in viscosity reported by these authors during long pasting has been attributed to the formation of ALCs.…”
Section: Resultscontrasting
confidence: 99%
“…The first peak viscosity of maize starch extrudates without stearic acid was higher than the first peak viscosity of maize starch extrudates with 1.5% and 4% stearic acid for the different screw configurations and screw speeds. Maphalla and Emmambux also reported that the first peak viscosity of maize and teff starches pasted without stearic acid was higher than the first peak viscosity of maize and teff starches pasted with stearic acid. This is also related to the lower WAI and lower particle size observed under the microscope.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations